Quantum Detector Tomography - Zhang, L; Coldenstrodt-Ronge, H; Datta, A; Walmsley, I (2013)
As quantum detectors evolve to become ever more sophisticated, their description in terms of a limited number of generic parameters falls short. An alternative description of the performance of a detector is provided by its positive-operator-valued measure (POVM). In this chapter we introduce a technique, quantum detector tomography, which allows us to experimentally reconstruct the POVM of the detector under test. Detailed examples on how to apply this technique to phase-insensitive detectors are given. We also discuss the challenges for the tomography of phase-sensitive detectors and possible solutions. © 2013 Elsevier Inc.